Views of undergraduates on Vikshit Bharat@2047 - Darji, Chirag; Rajesh Chauhan (The Scientific Temper, 2024)
With a view to studying the views of undergraduate students studying in various disciplines, i.e., Science, Commerce and Arts, the researchers have collected the opinions from the undergraduate students on various aspects of Vikshit Bharat mission in 2047. The variables of the study were male-female & rural and urban areas. The survey research method was used for the study, and the nature of the study was qualitative. The population of the study comprised all the students of Gujarat state, India and the sample of the study was simply a random sampling technique. The self constructed research tool was prepared and administered among the students. The research tool was descriptive. The experts validated the tool, and then the data were collected from the students. The students answered the questions in detail, and it was analyzed through content analysis. It was found from the study that there were certain factors affecting Vikshit Bhart and the Government and the people should initiate to resolve them at the earliest in order to complete the dream of Vikshit Bharat. Unemployment, poverty, quality of education etc, are to be addressed. The students of the undergraduate colleges were found dedicated and committed to contributing to the mission of Vikshit Bharat. There were also suggestions from the students on how India would be the Vikshit Bharat on or before 2047. It was suggested that the Government should bring more transparency in each work, one nation one rule, one tax, common act and civil code, no corruption and more dedication among the government system. Regional differences and gender differences were observed in the opinions.